Radish microgreens produced without substrate in a vertical multi-layered growing unit are rich in nutritional metabolites - Tilahun, Shimeles; Baek, Min Woo; An, Ki-Seok; Choi, Han Ryul; Lee, Jong Hwan; Hong, Jin Sung; Jeong, Cheon Soon (Frontiers in Plant Science, 2023)
Growing microgreens on trays without substrate in a vertical multilayered growing unit offers several advantages over traditional agriculture methods. This study investigated the yield performance and nutritional quality of five selections of radish microgreens grown in sprouting trays, without a substrate using only water, in an indoor multilayer cultivation system using artificial light. Various parameters were measured, including fresh weight, dry matter, chlorophyll, minerals, amino acids, phenolics, flavonoids, anthocyanins, vitamin C, glucosinolates, and antioxidant activity with four different in vitro assays. After ten days, the biomass had increased by 6-10 times, and the dry matter varied from 4.75-7.65 %. The highest yield was obtained from ‘Asia red’, while the lowest was from ‘Koregon red’. However, ‘Koregon red’ and ‘Asia red’ had the highest dry matter. ‘Asia red’ was found to have the highest levels of both Chls and vitamin C compared to the other cultivars, while ‘Koregon red’ exhibited the highest levels of total phenolics and flavonoids. Although variations in the levels of individual glucosinolates were observed, there were no significant differences in the total content of glucosinolates among the five cultivars. ‘Asia purple’ had the highest anthocyanin content, while ‘Asia green 2’ had the lowest. The K, Mg, and Na concentrations were significantly highest in ‘Asia green 2’, and the highest Ca was recorded in ‘Asia purple’. Overall, ‘Asia purple’ and ‘Koregon red’ were the best cultivars in terms of nutritional quality among the tested radish microgreens. These cultivars exhibited high levels of dry weight, total phenolics, flavonoids, anthocyanins, essential and total amino acids, and antioxidant activities. Moreover, the implementation of this vertical cultivation method for microgreens, which relies solely on water and seeds known for their tall shoots during the sprouting could hold promise as a sustainable approach. This method can effectively be utilized for cultivar screening and fulfilling the nutritional and functional needs of the population while minimizing the environmental impacts associated with traditional agriculture practices.